Promising directions using the management system railway traffic safety - Uvaliyeva А.Б.; Kisselyova О.Г.; Yeskozhanova Н.Г.; Сhen Юн (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The article is devoted to the actual issues of increasing the level of guaranteed traffic safety. The purpose of the article is to develop a systematic approach that allows to reduce the risk of traffic safety violations. The article shows the results of the analysis of the effectiveness of the measures that contribute to increasing the level of traffic safety implemented in railway transport. It has been determined that the implementation of a system approach is effective for achieving the goals of ensuring traffic safety. The systemic approach is based on the use of risk-management tools, the development of a positive safety culture and a process approach. The result of the study is the "Traffic Safety Matrix" consisting of two interdependent blocks. In Block 1, it is recommended to introduce the elements that support the transportation process - these are personnel, rolling stock and infrastructure. Block 2 includes elements that ensure traffic safety of the transportation process, technological process, service improvement, law enforcement and control. The provided matrix allows for effective planning and implementation of safety measures, monitoring of timely execution, monitoring of the effectiveness of measures used to assess the dynamics of the level and condition of traffic safety. "Traffic safety matrix" can be compiled on the basis of a systematic approach to technical, informational, material, human resources and capabilities of any institution of railway transport. This allows to adjust the actions of the participants in the transport process to the main result - increasing the level of traffic safety.